The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3233/jad-180624
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Frontotemporal Lobar Degeneration and Bullous Pemphigoid

Abstract: Recent studies have shown an epidemiological and immunological association between bullous pemphigoid (BP) and several neurological or psychiatric diseases. Here, our aim was for the first time to specify whether an association exists between BP and frontotemporal lobar degeneration (FTLD). Medical histories of FTLD patients (N=196) were screened for clinical comorbidity and BP180 and BP230 autoantibodies were analyzed in the sera of FTLD patients (N=70, including 24 C9orf72 repeat expansion carriers) by BP180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…First, an increased prevalence of autoimmune diseases has been reported in FTLD patients compared to controls [45][46][47] and second, FTLD seems to be inversely linked to cancer [48], which may suggest alterations in the immune system or responses. Interestingly, the contribution of autoimmune mechanisms and genetic variation in loci associated with the immune system in FTLD were also suggested in recent studies [15,[49][50][51]. In line with these patient-derived data, C9orf72 repeat expansion has been linked to disturbances in the immune system [52], e.g., in mouse models with loss of function of the C9orf72 gene, which indicate a severe autoimmune phenotype, high mortality rate, and increased levels of proinflammatory cytokines and signs of neuroinflammation [16,17,52,53].…”
Section: Discussionmentioning
confidence: 74%
“…First, an increased prevalence of autoimmune diseases has been reported in FTLD patients compared to controls [45][46][47] and second, FTLD seems to be inversely linked to cancer [48], which may suggest alterations in the immune system or responses. Interestingly, the contribution of autoimmune mechanisms and genetic variation in loci associated with the immune system in FTLD were also suggested in recent studies [15,[49][50][51]. In line with these patient-derived data, C9orf72 repeat expansion has been linked to disturbances in the immune system [52], e.g., in mouse models with loss of function of the C9orf72 gene, which indicate a severe autoimmune phenotype, high mortality rate, and increased levels of proinflammatory cytokines and signs of neuroinflammation [16,17,52,53].…”
Section: Discussionmentioning
confidence: 74%
“…Increasing evidence suggests that immune system alterations, including inflammation and autoimmunity, are associated with both sporadic and genetic forms of FTLD [4,10,12,26,27]. Several murine model studies have indicated that C9orf72 loss-of-function leads to severely altered peripheral inflammatory marker levels (cytokines, autoantibodies and peripheral blood counts) coinciding with autoimmune disease-like phenotypes and increased mortality [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory phenotypes were substantially more severe in total C9orf72 knock-out (−/−) mouse models, but heterozygous knock-out mice (+/−), modeling haploinsufficiency due to the C9orf72 HRE in human FTLD patients, also showed mild inflammatory alterations [1][2][3]. Moreover, studies in FTLD patients in general have indicated genetic association to immunoregulatory HLA regions [4,5], association with autoimmune conditions [9][10][11][12], and, on the other hand, decreased prevalence of cancer [13], all indicating potential systemic immune system alterations in FTLD.…”
Section: Introductionmentioning
confidence: 99%
“…BP is most common in elderly populations, and it has become a serious problem with increasing worldwide incidence due to increasing life expectancy in recent years 3–6 . Numerous reports have indicated a significant association between BP and neurological disorders 7–27 . However, the prevalence and significance of BP's associations with other comorbidities, including common systemic diseases, malignancies, and specific types of neurological disorders, such as stroke, Alzheimer's disorder, Parkinson's disorder, dementia, and multiple sclerosis (MS), have differed from one study to another 10–27 …”
Section: Introductionmentioning
confidence: 99%